Modelo para la selección de tecnologías de tratamiento biológico para aguas residuales institucionales SETBARI - Criollo Martínez, Ruby; Folleco, Blanca Lucía; Cuaspud, Rosa Elizabeth; Polo, Fabio David; Arroyo, Diana (Universidad y Salud, 2009)
During the formulation of the cleaning up and dumping management plan in the University of Nariño in Torobajo, it could be established that there are some differences between the municipals and institutional communities. However, it is possible to consider the sewage produced in an institution as domestic one, thus a modification of the “Modelo conceptual de selección de tecnología para el control de contaminación por aguas residuales domésticas SELTAR” is proposed for its application in institutional communities by taking into account the general differences between a municipal and an institutional community. The general schema is developed in a series of blocks composed by: feasibility, prioritization, environmental objectives (level of treatment of sewage) and sludge treatment. This schema is the support for the construction of a tool that allows selecting the best technological sustainable alternative considering the characteristics and the sewage quality, the uses of the source receptor, the costs of investment, operation and maintenance, as well as the socioeconomic and cultural characteristics of the institution.